An inferior source? Quantitatively analysing the production and revision of five technology-enhanced learning-related terms on Wikipedia - Michael Flavin; Katerina Hulova (Association for Learning Technology, 2018)
This article analyses five technology-enhanced learning-related terms on Wikipedia, assessing their usefulness in relation to academic journal articles concerning the same terms. Data were obtained about the word lengths of the Wikipedia articles, the numbers of Wikipedia edits and numbers of academic journal publications over the first 5 years after the creation of the first Wikipedia entry. Data were gathered directly from Wikipedia, as well as the academic journal aggregator Academic Search Complete, and were analysed in IBM SPSS 23. The article argues that Wikipedia can be more useful than academic journal articles in the new and emerging phases of a technology, because of the volume of information made available, together with the speed of its publication and the updating of its contents.